Spatial variability and changes of metabolite concentrations in the cortico‐spinal tract in multiple sclerosis using coronal CSI. Issue 3 (26th December 2012) - Tur, Carmen; Wheeler‐Kingshott, Claudia A.M.; Altmann, Daniel R.; Miller, David H.; Thompson, Alan J.; Ciccarelli, Olga
Abstract : We characterized metabolic changes along the cortico‐spinal tract (CST) in multiple sclerosis (MS) patients using a novel application of chemical shift imaging (CSI) and considering the spatial variation of metabolite levels. Thirteen relapsing‐remitting (RR) and 13 primary‐progressive (PP) MS patients and 16 controls underwent 1 H‐MR CSI, which was applied to coronal‐oblique scans to sample the entire CST. The concentrations of the main metabolites, i.e., N ‐acetyl‐aspartate, myo‐Inositol (Ins), choline containing compounds (Cho) and creatine and phosphocreatine (Cr), were calculated within voxels placed in regions where the CST is located, from cerebral peduncle to corona radiata. Differences in metabolite concentrations between groups and associations between metabolite concentrations and disability were investigated, allowing for the spatial variability of metabolite concentrations in the statistical model. RRMS patients showed higher CST Cho concentration than controls, and higher CST Ins concentration than PPMS, suggesting greater inflammation and glial proliferation in the RR than in the PP course. In RRMS, a significant, albeit modest, association between greater Ins concentration and greater disability suggested that gliosis may be relevant to disability. In PPMS, lower CST Cho and Cr concentrations correlated with greater disability, suggesting that in the progressive stage of the disease, inflammation declines and energy metabolism reduces. Attention to the spatial variation of metabolite concentrations made it possible to detect in patients a greater increase in Cr concentration towards the superior voxels as compared to controls and a stronger association between Cho and disability, suggesting that this step improves our ability to identify clinically relevant metabolic changes. Hum Brain Mapp 35:993–1003, 2014. © 2012 The Authors. Human Brain Mapping Published by Wiley Periodicals, Inc.